Analysis of the Cooperation of Islamic Religious Education Teachers (PAI) and Counseling Guidance Teachers (BK) in Improving Students' Morals - cahyani, anindita; Ayuningsih, Resti Fatma (Sekolah Tinggi Ilmu Tarbiyah Bustanul Ulum Lampung Tengah, 2025)
This study explores the collaboration between Islamic Religious Education (PAI) and Counseling Guidance (BK) teachers at SMK Al-Ikhsan Sukanegara in fostering students’ moral development. Employing a qualitative case study method, data were collected through interviews, observations, and documentation. The study reveals that PAI teachers focus on instilling moral and religious values through teaching and exemplary conduct, while BK teachers assist students through counseling services, character development programs, and preventive interventions. The synergy between the two disciplines plays a crucial role in addressing students' behavioral issues and promoting ethical awareness. Despite several obstacles, such as limited human resources, overlapping duties, and time constraints, the collaboration shows promising results due to regular communication, mutual support, and shared goals. The findings indicate that this partnership not only improves students' behavior and discipline but also enhances their spiritual and emotional intelligence. The study recommends strengthening institutional support and professional development to sustain and improve interdisciplinary collaboration in moral education. This model of cooperation between PAI and BK teachers can serve as a reference for other educational institutions aiming to integrate moral and counseling approaches in fostering students’ holistic character development.